My quitting stories: A qualitative study exploring Aboriginal women's experiences of smoking cessation and preventing relapse in the context of pregnancy. Issue 2 (March 2023) - Rahman, Tabassum; Weatherall, Alyce; Kennedy, Michelle; Baker, Amanda L.; Gould, Gillian S.
Abstract: Background: Most women who give up smoking during pregnancy relapse to smoking postnatally. Evidence on strategies that are helpful in maintaining smoking cessation during and beyond pregnancy is limited. Aim: This paper aims to explore Aboriginal women's experiences of quitting smoking, relapsing, and preventing relapse, focusing on the strategies they applied for attaining and maintaining abstinence and the support they received. Methods: Qualitative interviews were conducted between October 2020 and June 2021, in urban New South Wales, Australia, with 12 Aboriginal women who either smoked tobacco or quit smoking and had been pregnant in the last five years. Aboriginal Research Assistants recruited participants, participated in data collection and data analysis. Data were thematically analysed. Results: Major themes that emerged from the data include: a) aspiration to be abstinent; b) strong mindset; c) strategies to stay smoke-free; d) supports received; and e) service and policy recommendations. Protecting children from second-hand smoke had salience for the maintenance of abstinence. Having a strong mindset was perceived as a prerequisite to staying smoke-free. Use of multiple coping strategies in combination was frequently expressed. Knowledge about tobacco-related harms, the way nicotine dependence works, and the available support options was empowering and enabled informed decision making and actions around smoking cessation. Conclusion: This qualitative study conducted with 12 Aboriginal women revealed that Aboriginal women employ multiple strategies (cognitive, behavioural and social) to quit smoking and stay smoke-free. The strategies warrant further exploration with different Aboriginal communities across Australia and consideration of inclusion in smoking cessation care.